Integration of HIV and reproductive health services in public sector facilities: analysis of client flow data over time in Kenya. Issue 5 (14th September 2018) - Birdthistle, Isolde J; Fenty, Justin; Collumbien, Martine; Warren, Charlotte; Kimani, James; Ndwiga, Charity; Mayhew, Susannah
Abstract : Introduction: Integration of HIV/AIDS with reproductive health (RH) services can increase the uptake and efficiency of services, but gaps in knowledge remain about the practice of integration, particularly how provision can be expanded and performance enhanced. We assessed the extent and nature of service integration in public sector facilities in four districts in Kenya. Methods: Between 2009 and 2012, client flow assessments were conducted at six time points in 24 government facilities, purposively selected as intervention or comparison sites. A total of 25 539 visits were tracked: 15 270 in districts where 6 of 12 facilities received an intervention to strengthen HIV service integration with family planning (FP); and 10 266 visits in districts where half the facilities received an HIV-postnatal care intervention in 2009–2010. We tracked the proportion of all visits in which: (1) an HIV service (testing, counselling or treatment) was received together with an RH service (FP counselling or provision, antenatal care, or postnatal care); (2) the client received HIV counselling. Results: Levels of integrated HIV-RH services and HIV counselling were generally low across facilities and time points. An initial boost in integration was observed in most intervention sites, driven by integration of HIV services with FP counselling and provision, and declined after the first follow-up. Integration at most sites was driven by temporary rises in HIV counselling. The most consistent combination of HIV services was with antenatal care; the least common was with postnatal care. Conclusions: These client flow data demonstrated a short-term boost in integration, after an initial intervention with FP services providing an opportunity to expand integration. Integration was not sustained over time highlighting the need for ongoing support. There are multiple opportunities for integrating service delivery, particularly within antenatal, FP and HIV counselling services, but a need for sustained systems and health worker support over time. Trial registration number: NCT01694862